Tinjauan Literatur Peran SDLC dalam Pengembangan Sistem Informasi Manajemen Modern - Indah Siti Nurhalizah; Annur, Saipul; Rosad, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology encourages organizations to utilize Management Information Systems (MIS) to manage data and produce information effectively. The development of MIS requires a structured method so that the resulting system meets user needs. One of the methods used is the Software Development Life Cycle (SDLC). This study aims to examine the role of SDLC in the development of modern Management Information Systems through library research using a descriptive qualitative approach. The research data were obtained from books and scientific articles relevant to the topics of Management Information Systems and SDLC. The results of the study indicate that SDLC helps system development to be carried out systematically, resulting in more structured systems that meet organizational needs. Therefore, SDLC plays an important role in the development of modern Management Information Systems because it can produce systems that are effective and efficient.